Investigating the Immunogenicity of the BLF1 Antigen from Burkhordria Pseudomallei with PLGA Nanoparticle in Mice - Mahdi Dehati; Hossein Honari; Davoud Sadeghi; Seyed Mojtaba Aghaie (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: The bacterium Burkhordria pseudomallei causes melioidosis in humans and can be transmitted to the patients through oral ingestion, inhalation or skin scratches. The BLF1 protein from this bacterium stops protein synthesis within host cells. PLGA serves as a biodegradable polymer for incorporating various pharmaceutical and protein molecules. The aim of this study was to express the BLF1 protein in E. coli and load it into PLGA polymer, and investigate its immunogenicity in mice.Methods: In this research, the blf1 gene expression was induced by IPTG, and the presence of the recombinant protein was confirmed using the western blot technique. Antigen was loaded in PLGA polymer. The size and zeta potential of nanoparticles containing protein were measured. Protein with adjuvant; nanoparticles PLGA and PBS were administered to the groups of mice in two and four doses. The level of antibody in their serum was measured using the ELISA test. Ultimately, mice were exposed to BLF1 toxin. The data were analyzed utilizing SPSS 16 software. Results: PLGA nanoparticles with protein exhibited a higher PDI size and a more negative zeta potential compared to those without protein. The amount of protein loading in nanoparticles was about 95%. The results of the challenge test indicated 50% protection of the group with nanoparticles and 75% protection of the group with protein plus adjuvant. Conclusion: According to the administration frequency and the antibody titer of the recombinant protein with nanoparticles, along with the results obtained, this protein may be considered as a potential vaccine candidate for melioidosis.